Effects of Co-administration of Phytase and NSPase on Broiler Performance and Bone Ash - Coppedge, Jacob; Klein, Joseph; Brown, Blyn; Ratliff, Brent; Ruch, Frank; Lee , Jason T. (International Journal of Poultry Science, 2011)
An experiment was conducted to evaluate the effect of varying levels of phytase with and without NSPase inclusion on broiler performance when supplemented in corn/soy bean meal diets low in available phosphorus. The objective was to determine if NSPase inclusion enhances phytase activity in relation to growth parameters and bone ash in broilers reared in batteries through 14 days of age. Four diets with selected available phosphorus levels of 0.15, 0.20%, 0.25% and 0.30% were included in the experimental design to develop a dose response curve to calculate phosphorus release from experimental treatments. An addition six treatments were included that included three levels of phytase (150, 200 and 250 FTU/kg) with and without NSPase inclusion in a diet containing 0.15% available phosphorus. Evaluated parameters included body weight, feed conversion ratio and bone ash percentage. Body weight and bone ash percentage were positively influence with increases in available phosphorus levels. Phytase inclusion positively influenced growth performance and bone ash percentage. Broilers fed the 200 and 250 FTU/kg phytase inclusion levels outperformed the broilers fed the 150 FTU/kg inclusion level. Addition of NSPase with 150 FTU/kg phytase resulted in increased broiler body weight as compared to the 150 FTU/kg phytase diet alone. Using regression equations determined from dose response treatments for body weight, bone ash (mg) and bone ash percentage, NSPase inclusion increase phosphorus release at the 150 FTU/kg level from a 0.06% to 0.09%. These data indicate that NSPase inclusion may increase phytase effectiveness when co-administered during early stages of growth.